Алгебраїчне програмування інтеграції навчальних матеріалів в системах дистанційного навчання - Сотник, І. С. (ХНУРЕ, 2024)
The paper proposes a mathematical model for constructing the most optimal course of study for students based on finite predicates and predicate operations. The existing methods of determining the success of student learning are investigated. Variations of improving the algorithms for finding the appropriate structure of the training course based on the state graph are proposed. Considered different variants of implementation of the distance learning system in different educational institutions.
Keywords: алгебраїчне програмування; навчальні матеріали; дистанційне навчання